Penyebab Kerugian Terhadap Pembudidaya Ikan Keramba Jaring Apung di Waduk Saguling - Ageng Saepudin Kanda; Herdiana Nugraha (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
Cultivating fish using floating net cages (KJA) is a type of business that is quite promising, apart from that, the process of cultivating fish using floating net cages is not very difficult or can be said to be easy. However, there are many risks that can cause losses for entrepreneurs in cultivating floating net cage fish. The aim of this research is to find out the factors that cause losses in fish cultivation using floating net cages (KJA) in Saguling. The method used in this research is descriptive qualitative, where the data produced through interviews is expressed in the form of descriptions rather than numbers. The results found by the author in this research are that the biggest causes of losses experienced by floating net cage (KJA) fish farmers are caused by high fish mortality rates and selling prices that are not commensurate with the expensive price of feed.